RETRACTED: Simulation of the activation process for an activated carbon production plant - Safin R.G.; Sotnikov V.G. (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001